Quantification of Plasmodium falciparum Histidine-Rich Protein-2 in Cerebrospinal Spinal Fluid from Cerebral Malaria Patients - Mikita, Kei (The American Society of Tropical Medicine and Hygiene, 2014)
A cerebrospinal fluid (CSF) biomarker for cerebral malaria (CM) has not been validated. We examined the detection, semiquantification, and clinical use of the Plasmodium falciparum histidine-rich protein-2 (PfHRP-2) as a parasite antigen biomarker for CM. The PfHRP-2 was detected in archival CSF samples from CM patients from Tanzania both by a newly developed sensitive and specific immuno-polymerase chain reaction (72 of 73) and by rapid diagnostic tests (62 of 73). The geometric mean PfHRP-2 CSF concentration was 8.76 ng/mL with no differences in those who survived (9.2 ng/mL), those who died (11.1 ng/mL), and those with neurologic sequelae (10.8 ng/mL). All aparasitemic endemic and nonendemic control samples had undetectable CSF PfHRP-2. In a separate group of 11 matched plasma and CSF cerebral malaria patient samples, the ratio of plasma to CSF PfHRP-2 was 175. The CSF PfHRP-2 reflects elevated plasma PfHRP-2 rather than elevated CM-specific CSF ratios, falling short of a validated biomarker.